1970
DOI: 10.1002/pssa.19700010417
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of triboluminescence by deformation of single crystals

Abstract: The excitation of triboluminescence by elastic and plastic deformation and by fracture of single crystals has been studied in detail by means of a high sensitive experimental apparatus. Typical results are reported for crystals of ZnS(Mn), NaCl(Mn), X‐ray‐irradiated KI and KCl, and sugar. The experiments show that the characteristic light peaks of triboluminescence are intimately related to the treads occurring in the stress–strain curves. A detailed analysis of these curves in different materials suggests two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
62
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(62 citation statements)
references
References 11 publications
0
62
0
Order By: Relevance
“…Wick [3] also reported the ML emission during deformation of coloured alkali halide crystals. The linear dependence of light emission on the strain rate in -irradiated KBr, NaCl and LiF crystals was reported by Metz et al [4] and Alzetta et al [5]. The decrease in ML intensity with increasing rate of compression was reported by Pirog and Sujak [6].…”
Section: Introductionmentioning
confidence: 58%
“…Wick [3] also reported the ML emission during deformation of coloured alkali halide crystals. The linear dependence of light emission on the strain rate in -irradiated KBr, NaCl and LiF crystals was reported by Metz et al [4] and Alzetta et al [5]. The decrease in ML intensity with increasing rate of compression was reported by Pirog and Sujak [6].…”
Section: Introductionmentioning
confidence: 58%
“…These results follow Eqs. (15) and (16). The measurement of ML was done following the technique reported previously [39], in which the ML was induced by placing a load onto the crystal and the ML intensity was measured using a photomultiplier tube connected to an X-Y recorder.…”
Section: Article In Pressmentioning
confidence: 99%
“…Therefore, the materials exhibiting ML during their elastic deformation may be very useful and find applications in pressure sensors and other electronic devices. It has been reported that X or g-irradiated alkali halide crystals [14][15][16], Mn-doped zinc sulphide [16][17][18] and a few polymers [19,20] show ML when they are deformed elastically. Whereas the ML produced by the plastic deformation and fracture of coloured alkali halide crystals has been studied in detail [1][2][3], least attention has been paid to the ML induced by their elastic deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Pure zinc-sulfide is a noncentric [7] and exhibit ML [8]. Yet, when zinc sulfide doped with small percentage of strongly luminescent transition metal ions such as copper, manganese [9][10][11][12][13] and even silver [14], then it become strong mechanoluminescent under deformation. ZnS doped with Cu,Cl is found drastic enhance the mechanoluminescence (ML) properties [14].…”
Section: Introductionmentioning
confidence: 99%